Inhibitory Effects of Urtica thunbergiana Ethanol Extract on Atopic Dermatitis-Induced NC/Nga Mice - Hien T.T. Ngo; Minzhe Fang; Eunson Hwang; Yoosung Kim; Bom Park; Seul A Seo; Nhung Quynh Do; Quynh T.N. Nguyen; Tae-Hoo Yi (MDPI AG, 2020)
Atopic dermatitis (AD) is a chronic, inflammatory skin disease that persists or repeatedly recurs in both childhood and adulthood. Urtica thunbergiana (UT) is an aroma herb with little-known pharmacological effects and anti-inflammatory activities against AD. This study investigated the immunomodulatory efficacy of 50% ethanol-extracted UT in necrosis factor-alpha/interferon-gamma (TNF-α/IFN-γ)-stimulated HaCaT cells in vitro and AD-Biostir-induced NC/Nga mice in vivo. The results showed that UT exhibits a dose-dependent increase in scavenged free radicals, reaching 76.0% ± 1.4% of scavenged 1,1-diphenyl-2-picrylhydrazyl at a concentration of 250 µg/mL. In addition, UT significantly downregulated the mRNA expression of the following pro-inflammatory cytokines and chemokines in TNF-α/IFN-γ-stimulated HaCaT cells: interleukin (IL)-6, IL-8, thymus- and activation-regulated chemokine, macrophage-derived chemokine, and regulated on activation normal T expressed and secreted. UT-treated HaCaT cells showed inhibition of the overexpression of chemokine-regulated signaling molecules, such as nuclear factor-kappa B, inhibitor of kappa B (IκBα), signal transducer and activator of transcription 1, and mitogen-activated protein kinases (MAPKs). UT dietary administration in AD-Biostir-induced NC/Nga mice treated and improved AD-like symptoms, such as scales, epidermal thickening, the dermatitis severity score, high trans-epidermal water loss, reduced skin hydration, increased mast cells, elevated serum immunoglobulin E levels, and an enlarged spleen. UT treatment inhibited the expression of phosphorylated forms of MAPKs, nuclear factor of activated T-cells 1, and regulator IκBα. It also upregulated filaggrin (FLG) production. Therefore, UT shows high anti-AD activity both in vitro and in vivo, and can be a useful anti-AD agent.